Improvement of spectroscopic method for determining refractive index of filament sample material for 3D printing in terahertz range - Khoroshailo, Yu.Ye.; Zaichenko, N.Ya.; Zaichenko О.B. (Radiotekhnika, 2022)
The article considers the topical problem of non-destructive filament defectoscopy for 3D printing. The subject of the research is the process of determining the refractive index of the filament material for 3D printing taking into account the reflections from sample opposite walls, which is studied by terahertz spectroscopy in the time domain. Reflections from opposite walls are called the Fabry-Perot effect, and interference members resulting from reflections from walls are traditionally taken into account by summation and represented as a series. The disadvantage of the model in the form of a simple summation is the rejection of the members of the series above the fourth, which leads to inaccuracies in the model. The main problem with terahertz spectroscopy and this study in particular is the contradiction between the rapid development of terahertz spectroscopy and the slow development of models used in terahertz spectroscopy, while the adjacent microwave region has a set of ready-made models. Models based on the description of a standing wave in the microwave tract with refinements, transferred to a new region of terahertz spectroscopy in the time domain. The scientific novelty lies in increasing accuracy by taking into account previously unaccounted for interference members. The analogy between the Fabry-Perot effect used in terahertz spectroscopy and the reflections in a microwave multiprobe multimeter suggested the following recommendations. First, because the phase distance between the sensors in the microwave multimeter is similar to the thickness of the sample in terahertz spectroscopy, therefore, there was choosen such a sample thickness that the interference members are compensated, and secondly, instead of simple sum up it is possibility apply algorithmic processing, the condition for this is the existence in addition to the main signal in the time domain of the recorded echo signals of much smaller amplitude, therefore, one can build a system of equations and by solving it to determine the desired refractive index parameters of the filament sample material.